Idiopathic acquired sideroblastic anaemia transforming to acute myelosclerosis. Issue 9 (September 1984) - Bested, A C; Cheng, G; Pinkerton, P H; Kassim, O; Senn, J S
Abstract : A case of idiopathic acquired sideroblastic anaemia transforming to acute myelofibrosis is reported. The appearance of atypical megakaryocytic proliferation in idiopathic acquired sideroblastic anaemia may presage the development of an acute myelofibrotic phase of this usually chronic disease.